Eco-cement: Save the mother nature - Khairunisa, Muthusamy; Rahimah, Embong; Sharifah Maszura, Syed Mohsin; Nur Farhayu, Ariffin; Nabilla, Mohamad; Hanis Nadiah, Ruslan (2021)
Environmental pollution caused by disposal of solid wastes from fisheries industries along with increasing use of limestone for cement manufacturing in construction industry has led to the development of ECO-CEMENT. ECO-CEMENT is an environmental friendly cement formed by cockle shell powder as mixing ingredient. ECO-CEMENT give positive impact to the environment by reducing cockle shell dumping and reducing usage of limestone cement in construction sector. Adding powder cockle shell as partial cement replacement reduces cement use leading towards reduction of greenhouse gas released by cement industry.